1976
DOI: 10.1159/000197940
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Single Dose of Cyclophosphamide on the Jejunum of Specified Pathogenfree and Germfree Rats

Abstract: After a single dose of cyclophosphamide (100 mg/kg) cell proliferation in the jejunum of the rat decreased within the first 24 h and returned to the initial level after 48 h. Under the influence of cyclophosphamide, an increased cell loss in germfree rats could be observed. Villus height and villus cell count tended to decrease. Changes in disaccharidase activity in mucosal scrapings with respect to protein and DNA content could not be demonstrated. An influence of presence or absence of bacterial flora could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A more likely possibility may be that cyclophosphamide has a direct effect on the gut that brings about these changes. Although frank gut ileus has not been reported with cyclophosphamide, the drug is known to produce structural and functional changes in gut mucosal cells (3,6,10). Thus, it is conceivable that bacterial and candidal overgrowth may occur in a manner similar to that seen with blind loops or dysmotility syndromes (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…A more likely possibility may be that cyclophosphamide has a direct effect on the gut that brings about these changes. Although frank gut ileus has not been reported with cyclophosphamide, the drug is known to produce structural and functional changes in gut mucosal cells (3,6,10). Thus, it is conceivable that bacterial and candidal overgrowth may occur in a manner similar to that seen with blind loops or dysmotility syndromes (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for their location would be that the intestinal epithelium is an important site on the migration pathways of young T cells, perhaps because of the large amounts of antigen which may be present in the intestinal lumen (Ferguson, 1977). Although data on antigen excess, either microbial or alimentary, are not available, it is known that germ-free animals deprived of microbial antigens have low IEL counts (Glaister, 1973;Ecknauer and Lohrs, 1976) and that removal of food antigen from healthy animals does not induce a decrease of IEL counts (Ferguson, 1976); on the other hand, it is suggested that the increase of IEL counts in coeliac disease must be due to antigen stimulation (Mavromichalis et al, 1976). It might be hypothesised, therefore, that an increase of intestinal IEL could be occurring in malnutrition, in which intestinal infection, bacterial overgrowth in the small bowel, or partial digestion of food protein antigens is likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that the levels of Lactobacillus and Bifdobacterium were reduced, while Enterococcus and Escherichia coli were increased in the intestinal tract of mice treated with cyclophosphamide. Tis could be one of the reasons for the variations in the absorption of DMAG [39,40].…”
Section: Pharmacokinetic Studymentioning
confidence: 99%